Pengaruh Satisfaction, Serqual, Value, Trust, Switch cost, Corpimage Terhadap Customer Loyalty - Marcellinus Marcellinus; Tommy Setiawan Ruslim (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
This study aims to determine the effect of customer satisfaction, perceived service quality, perceived value, trust, perceived switching costs, and corporate image of customer loyalty. This study uses the reference theory of